Carbohydrate tolerance in Amazon tambaqui (Colossoma macropomum) revealed by NMR-metabolomics - Are glucose and fructose different sugars for fruit-eating fish? - Ferrari, Jeisson Emerson Casimiro [UNESP]; Palma, Mariana; Carli, Gabriela Castellani [UNESP]; Satiro, Thaise Mota [UNESP]; Tavares, Ludgero C.; Viegas, Ivan; Takahashi, Leonardo Susumu [UNESP] (Elsevier, 2022)
In the present study, two approaches were followed to evaluate the metabolic responses of tambaqui (Colossoma macropomum), a frugivorous species, to intraperitoneal (IP) administration of glucose (GLU) and fructose (FRU) in fed (FED) and 10-day fasted (FAST) fish. Glucose and fructose tolerance tests were performed to assess the carbohydrate utilization and complementary NMR-metabolomics analyses were done to elucidate the impacts of sugar mobilization on the metabolic profile of plasma, liver and muscle. Blood was sampled from FED groups at 0, 3, 6 and 24 h; and at 0 and 24 h from FAST groups. Significant differences were observed in the hyperglycaemic peak between sugars at 3 h (GLU - 13.7 ± 2.0 mM vs. FRU - 8.7 ± 1.1 mM; saline 6.3 ± 0.6 mM) and on the return to normoglycaemia (GLU - 8.5 ± 2.2 mM vs. FRU - 5.2 ± 0.9 mM; saline 4.9 ± 0.6 mM) 6 h after IP on the FRU fish. The NMR-metabolomics approach allowed to conclude that tambaqui seems to be more responsive to the feeding regime (FED vs. FAST) than to the injected sugar (FRU vs. GLU). From the studied tissues, plasma showed no significant variations between feeding regimes at 24 h after IP, while muscle and liver revealed some variations on the final metabolome profile between FED and FAST groups. The metabolome variations between feeding regimes are indicative of changes on the amino acid utilization. Fish from FAST group seem to utilize amino acids as energy source rather than for protein synthesis and muscle growth. Variations on glucose concentration in muscle can also indicate different utilization of the sugars depending on the feeding regime.
Keywords: Colossoma macropomum; Fasting; GTT; Hyperglycaemia; Intraperitoneal injection; Metabolomics